2013
DOI: 10.24925/turjaf.v1i2.67-72.34
|View full text |Cite
|
Sign up to set email alerts
|

Niğde İli Süt Sığırcılığı İşletmelerinin Mevcut Durumu, Başlıca Sorunları ve Çözüm Önerileri

Abstract: Bu çalışma, Niğde ili süt sığırcılığı işletmelerinin bugünkü durumunun ortaya konulması, öncelikli sorunların tespiti ve bu sorunların çözümüne ilişkin çeşitli önerilerin geliştirilmesi amacıyla yürütülmüştür. Çalışmada, ilin tamamını temsil edecek şekilde tabakalı örnekleme yöntemiyle seçilen toplam 95 süt sığırcılığı işletmesi örnek olarak alınmıştır. Analiz sonuçları; süt sığırı yetiştiricilerin büyük bir kısmının (%60) ilkokul mezunu, sığırcılık yapma süresinin ortalama 15,2 yıl olduğunu; işçilik olarak ön… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Köseman and Şeker (2016) reported that cattle farms in Malatya watering were practiced twice a day in 50.2% of the cattle farms and in 43.6% of the enterprises cattle had free access to water. In similar studies conducted in Turkey, it was reported that general cleaning practice was carried out in the cattle enterprises at least once, twice or more in a year (Ünalan et al, 2013;Aydın et al, 2016;Güler et al, 2017). conducted in other regions of Turkey (Tilki et al, 2013;Şahanoğlu and Koçak, 2014;Aydın et al, 2016;Demirhan and Yenilmez, 2019;Bakır and Kibar, 2020).…”
Section: Resultsmentioning
confidence: 96%
“…Köseman and Şeker (2016) reported that cattle farms in Malatya watering were practiced twice a day in 50.2% of the cattle farms and in 43.6% of the enterprises cattle had free access to water. In similar studies conducted in Turkey, it was reported that general cleaning practice was carried out in the cattle enterprises at least once, twice or more in a year (Ünalan et al, 2013;Aydın et al, 2016;Güler et al, 2017). conducted in other regions of Turkey (Tilki et al, 2013;Şahanoğlu and Koçak, 2014;Aydın et al, 2016;Demirhan and Yenilmez, 2019;Bakır and Kibar, 2020).…”
Section: Resultsmentioning
confidence: 96%